2022
DOI: 10.1155/2022/4156330
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effects and Molecular Mechanism of Total Flavonoids from Lycium Barbarum Leaves on Photoaged Human Dermal Fibroblasts

Abstract: Objective. To investigate the effects and corresponding mechanisms of total flavonoids (TFL) from Lycium barbarum leaves on photoaged human dermal fibroblasts (HDFs). Methods. Crude TFL was extracted with 70% ethanol, and a Rutin standard curve was drawn using the sodium nitrite-aluminum nitrate-sodium hydroxide colorimetry method to calculate its yield and mass concentration. After that, the photoaging HDFs model was established by UVA combined with 8-MOP. CCK-8 was performed to assess the influence of TFL on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…A recent study showed that, SOD and MDA are negatively correlated, which means that increasing the SOD activity reduces MDA content (Song et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that, SOD and MDA are negatively correlated, which means that increasing the SOD activity reduces MDA content (Song et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for this negative correlation is the accumulation of flavonoids. Flavonoids increases cell proliferation, SOD, and CAT activity, which inhibits oxidative stress (Song et al 2022). As SOD is present in almost all plants that generate activated oxygen, it has been predicted that SOD has a central role in oxidative (El-Beltagi & Mohamed 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar result was found in the study on flavonoids, one kind of metabolites in heat-killed probiotics. Song et al (2022) reported that total flavonoids from lycium barbarum leaves could decrease SA-β-gal-positive cell staining rate, thereby protecting against UVA-induced photoaging in human dermal fibroblasts [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…After vacuum filtration, the hydroethanolic extracts were concentrated at 40 °C by a rotary evaporator (SY-2000, Yarong Technology and Science Inc., Shanghai, China), then freeze-dried at −20 °C using a lyophilizer (FD-1A, Boyikang Experimental Instrument Co., Ltd., Beijing, China), and finally ground into powder (termed CFs). e sodium nitrite-aluminum nitrate method [19] was utilized to determine the content of CFs with a UV-Vis spectrophotometer (UV-2500PC, Shimadzu Co., Kyoto, Japan). e absorbance was measured at 510 nm, and the standard curve with reference substance of rutin was Y � 7.1105X-0.004 (R 2 � 0.9994), where Y is the absorbance and X is the concentration of rutin.…”
Section: Extraction Of Cfsmentioning
confidence: 99%